LIGHTWEIGHT REALIZATION METHOD FOR WHEEL-SIDE REDUCER BASED ON HIGH DURABILITY LEVEL - ZHENG SongLin; HUANG ChongWen; FENG JinZhi; HUA FeiFei (Jixie qiangdu)
The unsprung mass of an electric vehicle is increased because of the placement of electric driving system,which deteriorate the vehicle handling stability. Therefore,the light-weight design of the wheel-side reducer is a crucial problem that requires to be solved. The main topic of this paper is concerning light-weight design methodology for the reducer shell. The design objective is the satisfaction of high durability test life requirement while guarantee of rigidity and intensity requirements.Firstly,the main load and static strength were analyzed. Results showed that the max stress was far lower than the fatigue strength so that a light-weight design work was required. The allowable max working stress was calculated according to the fatigue life requirement. A structural optimization result was calculated by setting the max stress as the constraint and the minimum volume as the objective. Finally,the optimized shell’s fatigue life was predicted by applying virtual fatigue simulation method. The simulation results showed that the shell was furthest light-weight designed on the basis of satisfying specified durability test requirement.